Childhood cancers in southern Ethiopia 1963 - 1986 - Lindtjorn, Bernt (My University, 2020)
The pattern of childhood malignancies from southern Ethiopia is presented as it appears from a retrospective study of biopsy proven malignancies during the period 1963—1986. Retinoblastoma was the most frequently observed tumour, but lymphomas were also frequently observed. Hodgkin's Disease and Burkitt's lymphoma were the two most common lymphoma types .
Keywords: Cancer; children; Epidemiology; Ethiopia